Flexible conductive film with high substrate adhesion and preparation method and application thereof
By spin-coating the uncured PDMS film on the PDMS substrate material and spraying the carbon nanofiber solution under heating conditions, the problem of low interface stability between the substrate and the conductive material in the flexible sensor is solved, high interface stability and adhesion are achieved, and the stability and application performance of the sensor are improved.
Patent Information
- Application Number
- CN202510022111.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The low interface stability between the sensing layer substrate and the conductive material of existing flexible sensors hinders its effectiveness in practical applications.
By spin-coating the uncured PDMS film on the PDMS substrate material and spraying the carbon nanofiber ethanol solution under heating conditions, the two are integrated during heating and curing, the mechanical mismatch between the conductive material and the substrate is eliminated and interface adhesion is improved.
It realizes high interface stability and adhesion between the conductive material and the substrate, and improves the stability and practical application performance of the flexible sensor.
Smart Images

Figure CN119811751A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a flexible conductive film with high substrate adhesion, a preparation method and application thereof, and belongs to the technical field of flexible conductive films and preparation thereof. Background Art
[0002] The collection of human physiological electrical signals can directly reflect the health status of the human body. Long-term detection of physiological electrical signals can predict the occurrence of certain diseases and take timely countermeasures. At present, traditional rigid electronic devices are usually made of hard materials, which makes it difficult to meet the requirements of conformal adhesion of sensors to human skin, resulting in large errors in the monitored signals. At the same time, traditional medical electronic devices are bulky, time-consuming and labor-intensive to queue up, and cannot meet the needs of long-term monitoring. Therefore, flexible wearable electronic devices have emerged. Unlike traditional rigid electronic devices, they have the advantages of good flexibility, ductility, portability and free bending, and are widely used in medical health monitoring, sports and fitness and other fields. Among them, flexible sensors are an important part of flexible wearable electronic devices and a bridge for two-way communication between the human body and external devices. The high stability of the sensor is an inevitable requirement for long-term and accurate pressure detection in various practical application scenarios. However, the stability of existing flexible sensors still faces challenges, such as the low interface stability problem between the substrate of the sensing layer and the conductive material, which seriously hinders the practical application of flexible sensors. Summary of the invention
[0003] Aiming at the problem of low interface stability between a substrate and a conductive material of a sensing layer in an existing flexible sensor, the present invention provides a flexible conductive film with high substrate adhesion, a preparation method and an application thereof.
[0004] The technical solution of the present invention:
[0005] One of the objects of the present invention is to provide a method for preparing a flexible conductive film with high substrate adhesion, the method comprising the following steps:
[0006] (1) Spin coating an uncured PDMS solution on a hydrophobicized glass, vacuum degassing, heating and curing, and peeling off to obtain a PDMS film;
[0007] (2) An uncured PDMS solution is spin-coated on the PDMS film, and a carbon nanofiber ethanol solution is sprayed under heating conditions. After the spraying is completed, the solution is heated and cured to obtain a flexible conductive film with high substrate adhesion.
[0008] It is further defined that the glass hydrophobization treatment process in (1) is: plasma treatment and fluorination treatment are performed on the glass surface in sequence.
[0009] It is further defined that the plasma treatment is: in an oxygen atmosphere, 30 to 60 W, and a treatment time of 3 to 5 minutes.
[0010] It is further defined that the fluorination treatment is: using 1H,1H,2H,2H-perfluorooctyltrimethoxysilane vapor at 200° C. to treat the plasma-treated glass surface for 50 to 70 minutes.
[0011] It is further defined that the heating curing temperature in (1) is 90° C. and the time is 5 hours.
[0012] It is further defined that the uncured PDMS solution in (1) and (2) is prepared by mixing glue A and glue B in a mass ratio of 10 to 15:1.
[0013] It is further defined that the spraying in (2) is carried out at a temperature of 90 to 150°C.
[0014] It is further defined that the spraying process parameters in (2) are: a spraying angle of 80 to 100°, a spraying number of 15 to 22 times, and a carbon nanofiber ethanol solution concentration of 1 to 1.5 mg / mL.
[0015] It is further defined that the heating curing temperature in (2) is 120° C. and the time is 30 minutes.
[0016] A second object of the present invention is to provide a flexible conductive film having high substrate adhesion prepared by the above method.
[0017] A third object of the present invention is to provide an application of the above-mentioned flexible conductive film with high substrate adhesion, specifically used as a flexible sensing layer of a flexible piezoresistive sensor.
[0018] Beneficial effects:
[0019] The present invention first spin-coats an uncured PDMS film identical to its material on a PDMS substrate material, and then sprays a conductive material on the uncured PDMS film under heating conditions, utilizing the characteristics that the two can be integrated during heat curing, eliminating the mechanical mismatch between the conductive material and the substrate due to the delamination phenomenon, improving interfacial stability, and utilizing the interlocking structure between the sprayed conductive material and the uncured PDMS to improve the interfacial adhesion between the conductive material and the substrate. In addition, the present invention sprays a conductive material on the uncured PDMS film under heating conditions, improving the dispersibility of the conductive material, and avoiding the conductive material from settling in the uncured PDMS film. At the same time, the method can obtain good electrical conductivity under the condition that the carbon nanofiber specific gravity is relatively small compared to the blending composite method. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The process flow chart of preparing the flexible piezoresistive sensor of the present invention;
[0021] Figure 2 This is a cross-sectional scanning electron microscope image of the flexible conductive film prepared in Example 1;
[0022] Figure 3 This is a comparison diagram of the adhesion strength between the conductive layer and the substrate of the flexible conductive film prepared in Example 1 and Comparative Example 1;
[0023] Figure 4 Schematic diagram of the sensing mechanism of the flexible piezoresistive sensor prepared in Example 1;
[0024] Figure 5 This is a comparison diagram of sensing signals of the flexible piezoresistive sensor prepared in Example 1 under the same and different applied pressures;
[0025] Figure 6 The real-time response data of the flexible piezoresistive sensor prepared in Example 1 monitoring elbow bending;
[0026] Figure 7 The flexible piezoresistive sensor prepared in Example 1 monitors the real-time response data of the human body's standing gait. DETAILED DESCRIPTION
[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0030] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0031] Example 1
[0032] (1) Preparation of hydrophobic glass
[0033] In order to make the prepared PDMS membrane easy to peel off from the glass, the glass needs to be hydrophobicized. The detailed process is as follows:
[0034] First, the surface of the glass was subjected to plasma treatment, specifically, in an oxygen atmosphere at 30 W for 3 minutes.
[0035] Then, the glass surface was fluorinated at 200° C. using vapor generated by 1H,1H,2H,2H-perfluorooctyltrimethoxysilane (Aladdin Reagent Co., Ltd.) for 1 h.
[0036] Finally, wait for the hydrophobic glass to cool down and set aside.
[0037] (2) Preparation of flexible sensing layer
[0038] First, the uncured PDMS solution (PDMS, Dow Corning, USA, model is Sylgard 184, the mass ratio of precursor to curing agent is 10:1) is spin-coated onto the hydrophobic glass (spin-coating speed is 4000r / min), with a thickness of about 70μm. Secondly, in order to prevent the solution from being disturbed by bubbles, the uncured PDMS solution needs to be vacuum degassed for about 10 minutes. Thirdly, the glass with the spin-coated solution is placed in an oven and cured at 90°C for 5 hours, and the PDMS film is obtained by peeling.
[0039] Then, the uncured PDMS solution (PDMS, Dow Corning, USA, model is Sylgard184, the mass ratio of precursor to curing agent is 10:1) was spin-coated on the surface of the PDMS film, and a carbon nanofiber ethanol solution with a concentration of 1.5 mg / mL was sprayed while heating (120°C) (the carbon nanofiber was about 8 μm long and about 150 nm in diameter, and the manufacturer was Showa Denko of Japan), the spraying angle was 90°, and the number of spraying times was 20 times.
[0040] Finally, the film was cured at 120 °C for 30 min to obtain a flexible conductive film, in which the amount of carbon nanofibers was about 1.2 mg / cm 2 .
[0041] The cross-sectional microstructure of the obtained flexible conductive film was characterized, and the scanning electron microscope image of the cross section is shown in FIG. Figure 2 As shown, it can be seen from the figure that there is no delamination between the conductive layer and the substrate of the flexible conductive film, and the carbon nanofibers are evenly dispersed.
[0042] (3) Fabrication of flexible interdigitated electrodes
[0043] First, the pre-treated polyethylene terephthalate (PET, 0.5 mm thick) film was cut into a suitable size and mounted on the workbench of a screen printer (TP600S, Guangzhou Yuqi Machinery Co., Ltd.). The PET treatment process was to use acetone, ethanol and distilled water to ultrasonicate it for about 15 minutes to remove impurities on its surface.
[0044] Then, conductive ink (Deyang Encarbon Technology Co., Ltd.) was applied on one side of the template for printing.
[0045] Finally, the PET electrode film with the cross-finger conductive morphology was placed in an oven and dried at 70°C for 60 minutes for use. The number of interdigital pairs of the flexible interdigital electrode was 6, the interdigital width was 1 mm, the finger length was 19 mm, and the line spacing was 1 mm.
[0046] (4) Assembly of flexible piezoresistive sensor
[0047] The two ends of the prepared interdigital electrodes are connected to copper enameled wires, and then a flexible conductive film is placed on the interdigital electrodes and packaged to obtain a flexible piezoresistive pressure sensor. The specific preparation process is as follows: Figure 1 shown.
[0048] Comparative Example 1
[0049] The difference between this comparative example and Example 1 is that: in the step (2) of preparing the flexible sensing layer, an uncured PDMS solution (PDMS, Dow Corning, USA, model number is Sylgard 184, the mass ratio of precursor to curing agent is 10:1) is spin-coated on the surface of the PDMS film, the film is cured at 120°C for 30 min, and then a carbon nanofiber ethanol solution with a concentration of 1.5 mg / mL (the carbon nanofiber has a length of about 8 μm and a diameter of about 150 nm, and the manufacturer is Showa Denko of Japan) is sprayed, the spraying angle is 90°, and the number of spraying is 20 times to obtain a flexible conductive film; the remaining process steps and parameter settings are the same as those in the example.
[0050] The adhesion strength between the conductive layer and the substrate of the flexible conductive film prepared in Example 1 and Comparative Example 1 was tested. The specific testing method was to first adhere the conductive flexible film to the glass with glue, and then adhere the rigid wooden stick to the upper surface of the conductive flexible film with glue. Finally, a universal testing machine (manufacturer: Shenzhen Sansi Zongheng Technology Co., Ltd., model: UTM2501) was used to test the adhesion strength between the conductive material and the flexible film, and the irregular area adhered by the glue was calculated by ImageJ software. The results are shown in Figure 1. Figure 3As shown, it can be seen from the figure that compared with the comparative example 1 of directly spraying the conductive carbon nanofiber material onto the cured PDMS surface, the preparation method of Example 1 of spraying the conductive carbon nanofiber material on the uncured PDMS surface and then heating and curing the PDMS at the same time can effectively improve the adhesion strength between the conductive layer and the substrate.
[0051] The current response of the flexible piezoresistive sensor prepared in Example 1 under different pressures was tested, and the results are as follows: Figure 5 As shown in the figure, (a) is under different applied pressures, and (b) is under the same applied pressure. It can be seen from the figure that the sensing signal is consistent under the same and different applied pressures, indicating that the sensor has good stability, and the current response increases with the increase of applied pressure. This is because as the applied pressure increases, the contact area between the sensing layer and the interdigital electrodes will gradually increase, causing the contact resistance to decrease. At the same time, Figure 4 As shown in the figure, the applied pressure will cause the deformation of the sensing layer, and the distance between the conductive fillers in the flexible conductive film will be reduced to the quantum size (tunnel effect) or contact (percolation effect), which will then produce tunnel effect and percolation effect in the flexible conductive film, which further increases the resistance change of the flexible conductive film. Therefore, under the synergistic effect of the contact area change rate, tunnel effect and percolation effect, the current response will increase with the increase of applied pressure, which can effectively improve the sensitivity and detection range of the flexible piezoresistive sensor.
[0052] The flexible piezoresistive sensor prepared in the above Example 1 is further used for monitoring the elbow and standing gait. The specific monitoring method is to attach the sensor to different parts of the human body to measure the corresponding resistance change signal, and identify different motion states of the human body (such as monitoring the elbow and standing gait, etc.) by observing the signal monitored by the sensor during the movement. The results are as follows: Figure 6 and Figure 7 As shown in the figure, it can be seen that whether it is used for elbow or standing gait monitoring, the sensor has good stability, which is of great significance for human health monitoring.
[0053] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a flexible conductive film with high substrate adhesion, characterized in that: include: (1) Spin coating an uncured PDMS solution on a hydrophobicized glass, vacuum degassing, heating and curing, and peeling off to obtain a PDMS film; (2) An uncured PDMS solution is spin-coated on the PDMS film, and a carbon nanofiber ethanol solution is sprayed under heating conditions. After the spraying is completed, the solution is heated and cured to obtain a flexible conductive film with high substrate adhesion.
2. The preparation method according to claim 1, characterized in that: (1) The process of hydrophobizing the glass is as follows: the glass surface is subjected to plasma treatment and fluorination treatment in sequence.
3. The preparation method according to claim 2, characterized in that: The plasma treatment is: in an oxygen atmosphere, 30-60W, for 3-5 minutes; the fluorination treatment is: using 1H,1H,2H,2H-perfluorooctyltrimethoxysilane vapor at 200°C to treat the plasma-treated glass surface for 50-70 minutes.
4. The preparation method according to claim 1, characterized in that: (1) The heating curing temperature is 90°C and the time is 5 hours.
5. The preparation method according to claim 1, characterized in that: The uncured PDMS solution in (1) and (2) is prepared by mixing glue A and glue B in a mass ratio of 10 to 15:
1.
6. The preparation method according to claim 1, characterized in that: (2) Spraying is carried out at 90 to 150°C.
7. The preparation method according to claim 1, characterized in that: (2) The spraying process parameters are as follows: the spraying angle is 80-100°, the number of spraying times is 15-22 times, and the concentration of the carbon nanofiber ethanol solution is 1-1.5 mg / mL.
8. The preparation method according to claim 1, characterized in that: (2) The heating curing temperature is 120°C and the time is 30 minutes.
9. A flexible conductive film with high substrate adhesion prepared by the method of any one of claims 1 to 8.
10. Use of the flexible conductive film with high substrate adhesion according to claim 9, characterized in that: Used as a flexible sensing layer of a flexible piezoresistive sensor.
Citation Information
Patent Citations
Efficient preparation method for flexible ultra-extension conductive thin film based on one-dimensional nano material
CN105957639A
Elastic wearable strain sensor and preparation method thereof
CN106546161A
Flexible stress sensor based on carbon nanotube and silver nanowire composite conductive film
CN107655598A
Cited By
Flexible sensor based on silver nanowire material and preparation method and application thereof
CN120800441A